Species status of Centrolene lema Duellman and Señaris, 2003 (Amphibia: Centrolenidae) revealed by Integrative Taxonomy - Castroviejo-Fisher, Santiago; Guayasamin, Juan M.; Kok, Philippe J.r. (Zootaxa, 2009)
We evaluate the hypothesis of Centrolene lema as a species distinct from C. gorzulae using morphological, bioacoustic and genetic comparisons. Our results show that there are no consistent differences in any of these three areas; hence, we present C. lema as a synonym of C. gorzulae. Additionally we provide new data on the distribution and ecology of the species.